WORKING BY THE NUMBERS: PERFORMANCE ART SHORT ON TIME PROPOSES A MATERIALIST AESTHETICS OF PRODUCTION - Schmidt, Cecilie Ullerup (The Nordic Journal of Aesthetics, 2022)
The performance artists Florian Feigl and Fjóla Gautadóttir engage with production conditions of artistic work through their ways of managing time in performances. Informed by Marxist and feminist theories on affective and reproductive work, and with references to the history of performance art, I demonstrate how, contrary to myths of inspiration and virtuosity, production conditions co-create artistic authorship. Thereby, I reexamine what traditionally is termed as the aesthetics of production. An aesthetics of production is, I suggest, not about natural talent and originality of the soloist artist genius but is founded on the interdependency of life and work, and what enables the artist to do work. Feigl and Gautadóttir’s performances include what has been excluded as disturbances by idealist aesthetics of production: the sociality, temporality and economy of the artistic work. By proposing a feminist-materialist aesthetics of production, I claim that the artist’s work is not only working by the numbers of the present production conditions, but is also performing and intervening within the infrastructures of art.